2012
DOI: 10.1371/journal.pone.0035311
|View full text |Cite
|
Sign up to set email alerts
|

Particular Candida albicans Strains in the Digestive Tract of Dyspeptic Patients, Identified by Multilocus Sequence Typing

Abstract: Background Candida albicans is a human commensal that is also responsible for chronic gastritis and peptic ulcerous disease. Little is known about the genetic profiles of the C. albicans strains in the digestive tract of dyspeptic patients. The aim of this study was to evaluate the prevalence, diversity, and genetic profiles among C. albicans isolates recovered from natural colonization of the digestive tract in the dyspeptic patients.Methods and FindingsOral swab samples (n = 111) and gastric mucosa samples (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 51 publications
0
19
0
1
Order By: Relevance
“…Allelic concatenated nucleic acid sequences from 25 haemodialysis patient isolates, 47 control subject isolates, and 3256 reference strains retrieved from an MLST database were phylogenetically analysed by UPGMA. Clade numbers were assigned according to reference 41 . Three clades (10, 13, and 14) were not represented in isolates from either group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Allelic concatenated nucleic acid sequences from 25 haemodialysis patient isolates, 47 control subject isolates, and 3256 reference strains retrieved from an MLST database were phylogenetically analysed by UPGMA. Clade numbers were assigned according to reference 41 . Three clades (10, 13, and 14) were not represented in isolates from either group.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, these clades contain the fewest strains in the global C. albicans MLST database. No isolates in Clade 13 were found in studies from Chinese regions such as Beijing 37 , Chengdu 38 , Shanghai 39 , 40 , Shenyang 41 , and Taiwan 42 44 . Several earlier studies found strong evidence for a geographic influence in the low representation of some clades in certain regions of the world.…”
Section: Discussionmentioning
confidence: 99%
“…albicans isolates in the digestive tract of dyspeptic patients revealed a possible link between particular C . albicans genotypes and the host microenvironment [ 12 ]. For example, the C .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a study of C . albicans sampled from the digestive tract of dyspeptic patients was conducted in Shenyang [ 12 ]. However, no epidemiological study of C .…”
Section: Introductionmentioning
confidence: 99%
“…26,27 Furthermore, Candida albicans can grow well in highly acidic environments, 28 and some genotypes may increase the severity of gastric mucosal lesions. 29 Recently, a study using bacterial and fungal DNA co-sequencing analysis obtained 19-81 fungal genus-level operational taxonomic units in gastric juice, but only identified two fungal genera including Candida and Phialemonium. 30 Nevertheless, it is still uncertain whether gastric fungi or bacteria other than Helicobacter pylori participate in the pathogenesis of gastric diseases (e.g.…”
Section: Nature/classification Of Fungi In the Human Gi Tractmentioning
confidence: 99%